Fenologia reprodutiva e produção de sementes de Jatropha curcas L. - Herzog, Neusa Francisca Michelon (2012)
Pinhão-manso (Jatropha curcas L.) belonging to the Euphorbiaceae family from Americas has been disseminated in tropical and sub-tropical regions in the globe and also largely distributed in Asiatic and African continents. This specie has its seeds as the main way of spreading itself. Generally the reproductive material (seeds and fruit) is strongly influenced by the genitor plants, by the local climatic conditions that act on the development that comprises since the pollination process, the physiological maturity of the seed, to the plantation success. Due to its importance, this research aimed to characterize the flower and fruit production of the specie in an intercropped and monocultivation system, as well as to determine the production, the physical quality of the Jatropha curcas L. seeds, in Pato Bragado city in West of Paraná state. The study assessment period took 13 months and started in December 2010. The field experiment was set in areas of intercropped with Tifton and in a monocultivation system. The emission of floral buds and the flower and fruit abortion were weekly registered computing the formed fruit and quantifying the developed seeds. The number of locules was evaluated with formed seeds in fruitage, and some aspects related to the seeds were measured such as: the weight in grams, the length and the width in centimeters. The quality tests in the seeds were: germination in sand, germination speed index and tetrazolium test. The variance was analyzed by the Sisvar program, and the statistic difference between the average were compared by the Tukey test of 5% of error probability. The monocultivation favored the productivity. Four periods of flourishing were observed and the most expressive one occurred during the August to November period. The tendency to concentrate a bigger number of female flowers was noticed since the trees got older, and the most vigorous seed were produced during August to November period